Adoption of land administration domain model for land administration in Malaysia - Zulkifli, Nur Amalina (2014)
Land administration is a process of recording and disseminating information about the association between people and land. To administer land matters in Malaysia, the Department of Surveying and Mapping Malaysia uses eKadaster and Land Office has eTanah which are different e-systems. Currently, Malaysia does not have a standard model for land administration and standardisation is one of the important aspects in a land administration process. This research proposed a country profile model using international standards based on Land Administration Domain Model. This research also attempted to generate strata object model via Land Administration Domain Model which would be useful for Malaysia and countries with similar land administration systems. In this proposed model, spatial data modelling using secondary data from the aforementioned two land administration units in Malaysia and Unified Modelling Language application were used to develop the conceptual and the technical models. The developed model was evaluated and verified by the Department of Surveying and Mapping Malaysia and Land Office. These units agreed and were satisfied because the model fits their requirements by being more comprehensive as it included three-dimensional lots and two-dimensional topology. In addition, the proposed model facilitated the management of spatial and non spatial objects such as customary areas, reserved lands, lots, strata objects, utilities and the related attributes to be better managed by the two units. The development of Malaysian Land Administration Domain Model country profile is unique because it can support a very wide range of spatial units. Besides that, the profile included the contents of the various code lists as they are important aspects of standardisation. Furthermore, the model was developed to help establish a national Spatial Data Infrastructure or Malaysian Information Infrastructure. To conclude, the developed Malaysian Land Administration Domain Model is a standardised model that could be used for local and international exchange of information concerning land administration matters.